Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.scr.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

BDNF profoundly and specifically increases KCNQ4 expression in neurons derived from embryonic stem cells

Abstract: Neurons resembling the spiral ganglion neurons (SGNs) of the auditory nerve can be generated from embryonic stem cells through induced over-expression of the transcription factor Neurogenin-1 (Neurog1). While recapitulating this developmental pathway produces glutamatergic, bipolar neurons reminiscent of SGNs, these neurons are functionally immature, being characterized by a depolarized resting potential and limited excitability. We explored the effects of two neurotrophins known to be present in the inner ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…more hyperpolarized) RMP, which in our stem cell-derived neurons remained in the order of − 50 mV across the 5 weeks in vitro, is also suggestive of a maturing neural phenotype and may also be assisted by the presence of BDNF in the culture media (Purcell et al, 2013). As recently demonstrated by Purcell et al (2013), expression of the K + channel KCNQ4 dramatically increased in stem cell-derived neurons following BDNF exposure. These authors also reported a concomitant reduction in RMP, thereby highlighting the potential to produce specific neuronal subtypes using appropriate soluble molecules.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…more hyperpolarized) RMP, which in our stem cell-derived neurons remained in the order of − 50 mV across the 5 weeks in vitro, is also suggestive of a maturing neural phenotype and may also be assisted by the presence of BDNF in the culture media (Purcell et al, 2013). As recently demonstrated by Purcell et al (2013), expression of the K + channel KCNQ4 dramatically increased in stem cell-derived neurons following BDNF exposure. These authors also reported a concomitant reduction in RMP, thereby highlighting the potential to produce specific neuronal subtypes using appropriate soluble molecules.…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, the stem cell-derived neurons used by Chen et al (2012) displayed similar basic firing properties prior to their transplantation, to the stem cell-derived neurons described in the present study. Moreover, the voltage-gated ion channels that control neural activity are sensitive to changes in their environment, including concentration of neurotrophic factors (Adamson et al, 2002a;Zhou et al, 2005;Needham et al, 2012;Purcell et al, 2013) and excitatory input (Leao et al, 2005;Holt et al, 2006;Hassfurth et al, 2009), both of which are likely to play a role following their transplantation into the deaf cochlea. Determining how to harness and balance both in vitro and in vivo factors to derive functionally appropriate stem cell-derived neurons will be an important task in developing a stem cell therapy for the deaf cochlea.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been provided for a role of Ca V 3.1 voltage-gated L-type Ca 2+ channels in the differentiation of neural stem/progenitor cells [9] and of Kv3.1 K + channels in the proliferation and neuronal differentiation of adult neural precursor cells [43]. Expression of Kv7.4 channels was recently reported in neurons derived from embryonic stem cells [28], and a potential role of Kv7.2/7.3 channels in differentiation, synaptogenesis and synaptic function of mouse hippocampal and embryonic stem cell-derived neurons has been indicated [44]. …”
Section: Discussionmentioning
confidence: 99%
“…BDNF can increase the expression of potassium voltage-gated channel subfamily Q member 4 (KCNQ4) and it is necessary for the differentiation of neurons derived from ESCs into Spiral Ganglion Neuron (SGN) [58]. In a study, mouse ESCs (mESCs) were treated with the BDNF and glial cell line-derived neurotrophic factor after transient expression of Neurog 1 and 75% of neuronal cells derived from mESCs exhibited the glutamatergic phenotype after a 5-day culture in vitro.…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%